Gold nanomaterials as plasmonic layers to enhance power conversion efficiency of perovskite solar cell - Chia, Keith Hwa Kiat (Nanyang Technological University, 2021)
Mixed organic-inorganic halide perovskites are an emerging photovoltaic technology that has the potential to disrupt the mature silicon cell market. The promise of significantly lower production costs coupled with the perovskite solar cell’s (PSC) high absorption coefficient, tunable band-gap and long carrier lifetime has thus generated significant research interest in both the commercial and academic fields. However, the power conversion efficiency (PCE) of the PSC still falls short of the Shockley-Queisser limit as efficient absorption of light beyond the perovskite’s band-gap has yet to be demonstrated. Here we report on the effect of the incorporation of gold (Au) nanoparticles (NPs) as plasmonic layers between the PSC layers to improve the light-harvesting capability of the PSC through localized surface plasmon resonance (LSPR). Varying thickness of the Au film were deposited through Physical Vapor Deposition (PVD) and annealed under different tem- peratures to achieve thermal dewetting of the Au film for the formation of separated Au islands. The photovoltaic performance of the fabricated cells were then evaluated and studied through mor- phology, crystallographic and optical correlations. The PSCs showed an improvement from an av- erage PCE of 4.57% to 5.66% when an additional SnO2 layer was spin-coated between the Au and Cs0.05(MA0.17FA0.83)0.95Pb(I0.83Br0.17)3 layer. Although results demonstrated an overall decrease in the PCE as compared to the control, we elucidate the necessity of a capping layer surrounding the Au NPs in order to minimize surface recombination of the photo-generated excitons due to the formation of metal-semiconductor Schottky barriers. PCE of the best performing plasmonic-based device in this study was 11.54% by depositing Au between the TiO2 layers of the PSC.